Singularly perturbed integro-differential equations with degenerate Hammerstein’s kernel - Bobodzhanova, M.A.; Kalimbetov, B.T.; Safonov , V.F. (Bulletin of the Karaganda University. Mathematics Series, 2024)
Singularly perturbed integro-differential equations with degenerate kernels are considered. It is shown that in the linear case these problems are always uniquely solvable with continuous coefficients, while nonlinear problems either have no real solutions at all or have several of them. For linear problems, the results of Bobojanova are refined; in particular, necessary and sufficient conditions are given for the existence of a finite limit of their solutions as the small parameter tends to zero and sufficient conditions under which the passage to the limit to the solution of the degenerate equation is possible.